2013
DOI: 10.1182/blood-2012-04-422709
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and pathologic classification of children and adolescents with mediastinal large B-cell lymphoma treated with FAB/LMB96 mature B-NHL therapy

Abstract: Key Points• There are multiple histologic types of MLBCL in adolescents.• Event-free survival of MLBCL in adolescents after FAB/LMB 96 therapy is less compared to DLBCL. Mediastinal large B-cell lymphoma (MLBL) represents IntroductionMediastinal large B-cell lymphoma (MLBL) is a rare malignancy thought to arise from mature thymic B cells. Although previously considered by the World Health Organization (WHO) to be a subtype of diffuse large B-cell lymphoma (DLBCL), 1 primary mediastinal large B-cell lymphoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
62
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 36 publications
4
62
0
2
Order By: Relevance
“…One explanation for the relatively high incidence of extra nodal non Hodgkin lymphoma in this study (21 out of 44 cases) is increased frequency of gastrointestinal lymphomas in the Middle East. In the current study 3 year and 5 year survival were 48% and 30% respectively and median survival was 36 months which shows that there is a substantial survival difference from childhood and adolescents non Hodgkin lymphoma between Shahid Sadoughi Hospital in Yazd and many developed countries (Fukano et al, 2012;Gerrard et al, 2013;Lee et al, 2013). For example Lee et al showed that the 5-year failure-free survival, event-free survival, and overall survival rates were 86.7±2.9%, 79.1±3.5%, and 84.7±3.1%, respectively in children with non Hodgkin lymphoma (Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for the relatively high incidence of extra nodal non Hodgkin lymphoma in this study (21 out of 44 cases) is increased frequency of gastrointestinal lymphomas in the Middle East. In the current study 3 year and 5 year survival were 48% and 30% respectively and median survival was 36 months which shows that there is a substantial survival difference from childhood and adolescents non Hodgkin lymphoma between Shahid Sadoughi Hospital in Yazd and many developed countries (Fukano et al, 2012;Gerrard et al, 2013;Lee et al, 2013). For example Lee et al showed that the 5-year failure-free survival, event-free survival, and overall survival rates were 86.7±2.9%, 79.1±3.5%, and 84.7±3.1%, respectively in children with non Hodgkin lymphoma (Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In another study the estimated event-free survival at 5 years of 76.2±6.6was reported by Fukano et al, (Fukano et al, 2012). Mary Gerrard revealed that the 5-year overall survival in the 42 children and adolescents with non Hodgkin lymphoma was 73% (95%CI, 56%-84%) (Gerrard et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This point is clearly made by Gerrard and colleagues, who report a 5-year event-free survival (EFS) rate of 66% for stage III patients with MLBL compared with 85% for those with stage III non-MLBL DLBCL, treated with the same regimen. 1 As the authors point out, there is clearly a need to consider a new paradigm in our therapeutic approach to this disease, particularly with respect to younger patients.…”
mentioning
confidence: 99%
“…Gerrard and colleagues emphasize this dilemma and note that in some cases there was insufficient tissue available for the comprehensive immunophenotyping needed to distinguish between these subtypes in their retrospective review of pathology. 1 For personal use only. on May 11, 2018. by guest www.bloodjournal.org From matter?…”
mentioning
confidence: 99%
See 1 more Smart Citation